Demand Analysis for Major Consumer Commodities in Jordan - Akram Masoud Haddad (STIE Malangkucecwara, 2013)
The objectives of this research is to analysis the demand pattern, estimates the demand function for the necessary commodities in Jordan. Data from household expenditure and income surveys (HEIS) for the years 1992, 1997, 2000, 2003, 2006, 2008 and 2010 are utilized for comparisons, and to draw a sample of (700) household which represent (5%) of the total population of (HEIS) in 2010 in order to analysis the demand of the main commodities. The study finds that there are significant differences between both governorates and among years and there are decrease in percentages of expenditure on food items during the period of study. Moreover, the own-price and expenditure elasticities are consistent with economic theory excluding meat and eggs, the expenditure elasticities for vegetables, fruits and vegetable oils and fats are greater than one while for milk and its products is one. The other groups have expenditure elasticities less than one. The result of study can be considered as useful information for policy analysis such as price support and nutrition policy.